D‐Cysteine Ligands Control Metal Geometries within De Novo Designed Three‐Stranded Coiled Coils. Issue 34 (26th May 2017) - Ruckthong, Leela; Peacock, Anna F. A.; Pascoe, Cherilyn E.; Hemmingsen, Lars; Stuckey, Jeanne A.; Pecoraro, Vincent L.
Abstract: Although metal ion binding to naturally occurringl ‐amino acid proteins is well documented, understanding the impact of the opposite chirality (d ‐)amino acids on the structure and stereochemistry of metals is in its infancy. We examine the effect of ad ‐configuration cysteine within a designedl ‐amino acid three‐stranded coiled coil in order to enforce a precise coordination number on a metal center. Thed chirality does not alter the native fold, but the side‐chain re‐orientation modifies the sterics of the metal binding pocket.l ‐Cys side chains within the coiled‐coil structure have previously been shown to rotate substantially from their preferred positions in the apo structure to create a binding site for a tetra‐coordinate metal ion. However, here we show by X‐ray crystallography thatd ‐Cys side chains are preorganized within a suitable geometry to bind such a ligand. This is confirmed by comparison of the structure of Zn II Cl(CSL16D C)3 2− to the published structure of Zn II (H2 O)(GRAND‐CSL12AL16L C)3 − .1 Moreover, spectroscopic analysis indicates that the Cd II geometry observed by usingl ‐Cys ligands (a mixture of three‐ and four‐coordinate Cd II ) is altered to a single four‐coordinate species whend ‐Cys is present. This work opens a new avenue for the control of the metal site environment in man‐made proteins, by simply altering the binding ligand with its mirror‐imagedd configuration. Thus, the use of non‐coded amino acids in the coordination sphere of a metal promises to be a powerful tool for controlling the properties of future metalloproteins. Abstract : Cysteine in the mirror : The effect of changing the configuration of an amino acid froml tod within metal‐binding peptide sequences is investigated. By substitutingl ‐Cys withd ‐Cys residues a new binding situation for metal ions was created (see figure). This observation opens new possibilities for protein designers to control the properties of future metalloproteins.